(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2024)
There is a structural proximity between the concept of the sublime and that of anguish; a proximity that, however, does not prevent the scene from being very different in terms of the affects involved. With regard to structure, at stake is a field that involves the pulsating, differential simultaneity of absence and presence, death and life. The principle of mutual exclusion is replaced by the logic of contradictory inclusion. I will limit myself, in this context, to recounting a brief stretch of the history of the sublime, little travelled, in which the juxtaposition with anguish, a heterozygotic twin, brings to the fore the sameness of their structure - centred on the synchrony of opposites - and the inversion of the affects involved. The authors I will summon, in this brief stretch, are Jean-François Lyotard, as regards the sublime, and Jacques Lacan, as regards anguish. The theory of the sublime and that of anguish are frequently accompanied by the metaphorical evocation of membranes, tissue partitions. In what sense do the feeling of the sublime and the affection of anguish have to do with these tissue lacerations that, although belonging to the body, are, in truth, hors-corps? They are organs or parts of organs with such a slender structure as to be almost unreal, they are freed and go their own way, bearers of a pure life that slips and swirls, to the point of disquieting for a trait of immortality that they carry with them.